Support, interventions and outcomes for families/carers of people with borderline personality disorder: A systematic review. (30th December 2019) - Sutherland, Ruth; Baker, John; Prince, Sharon
Abstract: It is clear from existent literature that families and carers of relatives and friends with borderline personality disorder (BPD) experience high levels of burden. Whilst family interventions are considered vital to improving the outcomes of those with a range of mental health difficulties, there has been limited development of direct interventions for carers of people with BPD, despite a high level of need. This systematic review aimed to appraise and synthesize the existing research evidence for interventions for carers of people with BPD. Ten studies were included that were directly related to six interventions for families and carers of people with personality disorder. The findings of these studies, whilst limited, do provide some initial evidence that interventions for carers may lead to significant outcomes for the participants, particularly in improving carer well‐being and reducing carer burden. © 2019 John Wiley & Sons, Ltd.